Survey on the presence of integrons in Edwardsiella ictaluri, the causative agent of bacillary necrosis on intensively farmed striped catfish (Pangasianodon hypophthalmus) in the Mekong Delta - Van Cao Thi, Quach; Huynh, Trang Thi Diem; Tu, Dung Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
The purpose of this research was to evaluate the presence of the integrons and characterise the gene cassette regions in E. ictaluri that causes bacillus necrosic of Pangasius on striped catfish ( Pangasianodon hypophthalmus ) in the Mekong Delta. By using PCR technique and gene sequencing, the finding identified 24/67 (35,82%) class 1 integron-positive E. ictaluri strains. Meanwhile, no class 2 and 3 integrons were detected in the study. Besides, our result also found many different gene cassette regions (0,65 kbp, 0,8 kbp, 0,95 kbp, 1,0 kbp, 1,2 kbp, 1,5 kbp and 2,5 kbp ) encoding to dihydrofolate reductase, aminoglycoside adenyltransferase, aminoglycoside N(6')-acetyltransferase and β-lactamase enzymes resistant to different antibiotics in E. ictaluri . The presence of the mobile genetic elements (class 1 integrons) in E. ictaluri in this research showed the ability that bacteria can transfer antimicrobial resistance genes to other bacteria in the aquatic environment. Therefore, using antibiotics for disease prevention in aquaculture should be managed more strictly